A blind child in my Classroom : A handbook for primary teachers - Cronin, Peter. (RVIB, 1990)
The purpose and format of this book is identical to the original one: it is a compendium of answers to the questions most frequently asked by teachers; it provides useful pre-reading for teachers who have been asked to include a visually impaired child in their classroom and continues to be a resource for them during those times when the visiting teacher is not present.